2016
DOI: 10.1177/0894486516646917
|View full text |Cite
|
Sign up to set email alerts
|

Technological Innovation Inputs, Outputs, and Performance

Abstract: The aim of this research is to study the moderating role of family management in the relationships between the intensity of research and development and the occurrence of continuous technological innovation and between the existence of technological innovation outcomes and long-term firm performance. The results show that family management reduces efficiency in the conversion of research and development expenses into technological innovation outcomes over time. Our findings also suggest that the influence of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 96 publications
1
38
0
1
Order By: Relevance
“…Some short-term inefficiencies detected in the literature can be corroborated. The case under analysis confirms strong direct influence and control from the family, clearly signaled in both network analyses, endorsing findings in the literature about the family managers unwillingness to cede control (Diéguez-Soto et al, 2016). Particular TMM functions such as surveillance and enabling welcome STI partnerships and external knowledge, which is an indicator of the firm reliance on partners to identify new technologies and make their development a reality, as indicated by Alberti andPizzurno (2013), De Massis et al (2013) and Classen et al (2012).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Some short-term inefficiencies detected in the literature can be corroborated. The case under analysis confirms strong direct influence and control from the family, clearly signaled in both network analyses, endorsing findings in the literature about the family managers unwillingness to cede control (Diéguez-Soto et al, 2016). Particular TMM functions such as surveillance and enabling welcome STI partnerships and external knowledge, which is an indicator of the firm reliance on partners to identify new technologies and make their development a reality, as indicated by Alberti andPizzurno (2013), De Massis et al (2013) and Classen et al (2012).…”
Section: Resultssupporting
confidence: 82%
“…From a family firm research perspective, which emphasizes the family's strong influence on the firm's decision-making process (De Massis, Frattini, & Lichtenthaler, 2013;Diéguez-Soto, Manzaneque, & Rojo-Ramírez, 2016), management innovation starts with the family owners. As a socially bounded organization, all flow of activities, integration of innovative work and emotional impulse to innovate go through the family (Dougherty, 2008).…”
Section: The Management Of Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has shown that family firms may compete successfully in technologically rich environments and, more importantly, that the family and its knowledge are a fundamental resource for this success (Eddleston et al 2008;Basco 2014;Diéguez-Soto et al 2016;Llach et al 2012). However, research to date has neglected to provide a deeper understanding of how family-specific resources Baffect their propensity toward technological innovation and, more generally, their business behavior in technological innovation^ (De Massis et al 2013, p. 21).…”
Section: Introductionmentioning
confidence: 99%